Teacher Discomfort: Reflections on the Low Academic Performance of University Students - Vértiz-Osores, Jacinto Joaquín (2019)
The present research examined reflexively the causes of teacher discomfort linked to the negative results of students’ performance.   It was carried out under a qualitative approach with multiple case study design subjecting 10 university teachers to in-depth interviews.The results were disaggregated into the following categories: predominance of contradictory feelings; inability to endure  anxiety; inhibition; self- depreciation; anxiety as a dominant trait and balance; acceptance of conflict as an objective reality. It was concluded that the interviewees agreed on a contradiction between the higher education system to promote quality and the real provision of the tools and conditions to do so in practice. They manifested positions of lethargy conditioned by the need to work for the provision of resources, but with the awareness of the relevance of their social role as educators of a generation of students who require methodologies that challenge and encourage creativity in a digital education context.